2017
DOI: 10.3389/fneur.2017.00581
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and Local Cytokine Profile following Spinal Cord Injury in Rats: A Multiplex Analysis

Abstract: Our study of the changes in cytokine profile in blood serum and in the spinal cord after traumatic spinal cord injury (SCI) has shown that an inflammatory reaction and immunological response are not limited to the CNS, but widespread. This fact was confirmed by changes detected in a cytokine profile in blood serum samples [MIP-1α, interleukin 1 (IL-1) α, IL-2, IL-5, IL-1β, MCP-1, RANTES]. There were also changes in the levels of MIP-1α, IL-1α, IL-2, IL-5, IL-18, GM-colony-stimulating factor, IL-17α, IFN-γ, IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 42 publications
5
64
1
1
Order By: Relevance
“…A potential explanation for this paradox is that IL-6 results in a more transient STAT3 activation, whereas IL-10 results in a more sustained activation [8], perhaps due to negative feedback from SOCS family members after IL-6 activation but not IL-10 [103]. Interestingly, expression of IL-4 and IL-10, along with most other antiinflammatory cytokines, exhibit transient and acute expression after SCI [22,46,63], which may contribute to the prevalence of M1-like macrophages that persist chronically at the injury site. Accordingly, exogenous administration of IL-4 can promote M2-like polarization that is associated with improved histopathology and behavioral outcomes [22].…”
Section: Transcriptional Regulation Of Macrophage Polarizationmentioning
confidence: 99%
“…A potential explanation for this paradox is that IL-6 results in a more transient STAT3 activation, whereas IL-10 results in a more sustained activation [8], perhaps due to negative feedback from SOCS family members after IL-6 activation but not IL-10 [103]. Interestingly, expression of IL-4 and IL-10, along with most other antiinflammatory cytokines, exhibit transient and acute expression after SCI [22,46,63], which may contribute to the prevalence of M1-like macrophages that persist chronically at the injury site. Accordingly, exogenous administration of IL-4 can promote M2-like polarization that is associated with improved histopathology and behavioral outcomes [22].…”
Section: Transcriptional Regulation Of Macrophage Polarizationmentioning
confidence: 99%
“…When compared to sham conditions, spinal cords from SCI mice had significantly increased levels of IL-10 in comparison to 4 days, 5 days, and 7 days sham conditions (one-way ANOVA, Bonferroni's multiple comparisons test; * * * p < 0.001, * * p < 0.005, * * p < 0.005, respectively. As a positive control, we tested cuprizone-treated mice (a model of multiple sclerosis), which are known to secrete proinflammatory cytokines at the end of 5 weeks of treatment (Mukhamedshina et al, 2017). Cuprizone-treated mice showed expected increases in levels of TNF-α, IL-1β, and IL-10 in comparison to naïve controls (one-way ANOVA, Bonferroni's multiple comparisons test; * p < 0.05, * * p < 0.005, * * p < 0.005, respectively; Schmitz and Chew, 2008).…”
Section: Characterization Of Behavioral and Inflammatory Phenotypes Omentioning
confidence: 99%
“…During acute phase, SC expresses high amounts of Th1 phenotype which is mainly regulated by IL-2, IL-12 and IFNy. Moreover, in subacute phases IL-4, IL-13, IL-10, IL-17 and IL-23 cytokines are found in plasma and spleen, indicating the presence of Th2, Treg and Th17 profiles as an inefficient compensatory mechanism [93,94]. Accordingly to this, for the last 10 years experimental findings have shown that T lymphocytes are not just pathogenic but beneficial.…”
Section: Lymphocytes As Double-edged Sword In Spinal Cord Injurymentioning
confidence: 92%